A new phenyldilactone from Lespedeza cuneata. Issue 2 (1st February 2016) - Jiang, Wei; Ye, Ji; Xie, Yang-Guo; Pan, Ya-Ping; Zheng, Yue; Qian, Xiu-Ping; Jin, Hui-Zi
Abstract : A new phenyldilactone, maysedilactone B (1 ), together with twenty known compounds, were isolated from the aerial parts of Lespedeza cuneata . The structural elucidation of the isolated compounds was primarily based on HR-ESI-MS, IR and 1D and 2D NMR analyses. Compounds1 –8 and15 –21 were tested for cytotoxicity against four human tumor cell lines (A549, HCT116, SKOV3, and HepG2) using MTT method in vitro, while no significant activities were observed for the evaluated compounds.